Tikkun Olam. The Jewish vision of „Repairing the world” and its ecological explications - Nowicka, Barbara (Studia Ecologiae et Bioethicae, 2017)
In Jewish theology and philosophy, the problem of nature seems to be hidden, nature seems to be in the shadow of a man. However, the fact of environmental degradation undoubtedly has a huge impact on man. That is why ecology and the environment are becoming a problem that increasingly appears in Jewish thought. Jewish environmental protection is often connected with the concept of Tikkun Olam, which means repairing the world or restoration of the world. The Biblical roots of Tikkun Olam encourage us to study the meaning of nature and man in it. So we are instructed what is the place of man in the natural environment and what is our task in terms of nature. The concept of Tikkun Olam obliges us to permanent activities for nature that we should improve and take care of it. The biblical message and its transcendent source may be much stronger than human law. Therefore, the Judaic vision of ecology can also be an interesting proposition in the approach to care for the environment.